Changes in proteins in saliva and serum in equine gastric ulcer syndrome using a proteomic approach - Muñoz Prieto, Alberto; Contreras-Aguilar, Maria Dolores; Cerón, Jose Joaquín; Ayala, Ignacio; Martin-Cuervo, Maria; González Sánchez, Juan Carlos; Jacobsen, Stine; Kuleš, Josipa; Beletić, Anđelo; Rubić, Ivana; Mrljak, Vladimir; Tecles, Fernando; et al. (Animals, 2022)
Changes in the salivary proteome in 12 horses with the two diseases included in equine gastric ulcer syndrome (EGUS), equine glandular gastric disease (EGGD) (n = 6) and equine squamous gastric disease (ESGD) (n = 6), were evaluated using a high-resolution LC-MS/MS analysis of TMT-labelled peptides and compared to 10 healthy control horses. Serum was also analysed for comparative purposes. The comparison between the horses with EGGD and controls showed significant changes in 10 salivary proteins, whereas 36 salivary proteins were differently abundant between ESGD and control groups. The most upregulated proteins in the case of EGGD were related to immune activation whereas, in horses with ESGD, the most significantly changed proteins were associated with squamous cell regulation and growth. Compared to serum, saliva showed a higher number of proteins with significant changes and a different pattern of changes. The proteins identified in our study, in addition to providing new information about the pathophysiological mechanisms in these diseases, could have the potential to be novel biomarkers for the diagnosis or monitoring of EGGD and ESGD.